Maternal age at menarche and offspring body mass index in childhood - Hui Wang; Yunting Zhang; Ying Tian; Fei Li; Chonghui Yan; Hui Wang; Zhongchen Luo; Fan Jiang; Jun Zhang (BMC, 2019)
Abstract Background Earlier age of menarche has been associated with an increased risk of chronic diseases during adulthood, but whether early menarche has intergenerational effect is not clear. Methods In this population-based cross-sectional study, we recruited children from 26 primary schools using cluster random probability sampling in Shanghai, China, in 2014. We used multiple linear regression models to estimate the adjusted associations of maternal age of menarche (MAM) with offspring body mass index (BMI). We also used the mediation analysis to examine the contribution of maternal BMI and gestational diabetes to offspring BMI. Results A total of 17,571 children aged 6-13 years were enrolled, of whom 16,373 had their weight and height measured. Earlier MAM was associated with higher child BMI in boys (− 0.05 z-score per year older MAM, 95% CI − 0.08 to − 0.02) and in girls (− 0.05 z-score per year older MAM, 95% CI − 0.07 to − 0.02). Maternal BMI positively mediated the association of MAM with offspring BMI in both sexes, with mediation effects of 37.7 and 19.4% for boys and girls, respectively. Conclusion Early maternal menarche was associated with greater offspring BMI. This study provides evidence for the intergenerational effect in the development of BMI in offspring.